2021
DOI: 10.5219/1482
|View full text |Cite
|
Sign up to set email alerts
|

The quality characteristics of sausage prepared from different ratios of fish and duck meat

Abstract: The article aims to determine the effect of combining duck meat (Anas platyrhynchos) and freshwater fish (Hypophthalmichthys molitrix) on the quality (nutritional value, functional and technological properties, sensory attributes) of meat-containing semi-smoked sausages. The optimal version of the recipe with the highest quality indicators of semi-smoked meat sausages with duck meat and freshwater aquaculture was determined. It was found that the protein content of meat-containing, semi-smoked sausages with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It was established that when 10 % of beef is replaced with a similar amount of hemp flour in the formulation of chopped meat semi-finished products, the consumer properties of the finished product are preserved while increasing its biological value. It was determined in [18] that by combining pork with protein-containing raw fish and hemp seed protein in meat-rich cooked-smoked sausages, it is possible to produce high-value products with high quality. However, there are no data on the use of hemp processing products in the technology of baked meat-containing products, including traditional types of meat (pork) and products from secondary processing (MPSP).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It was established that when 10 % of beef is replaced with a similar amount of hemp flour in the formulation of chopped meat semi-finished products, the consumer properties of the finished product are preserved while increasing its biological value. It was determined in [18] that by combining pork with protein-containing raw fish and hemp seed protein in meat-rich cooked-smoked sausages, it is possible to produce high-value products with high quality. However, there are no data on the use of hemp processing products in the technology of baked meat-containing products, including traditional types of meat (pork) and products from secondary processing (MPSP).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In contrast to [48], where a decrease in the concentration of aldehydes is achieved due to polyphenols of seaweed, it was found that the use of polyphenols of chokeberry can reduce PN by almost 40 %. Of particular importance is the effectiveness of berry extracts for inhibition of the accumulation of secondary oxidation products when using them as part of multicomponent meat-containing products, including ingredients of various origins [49].…”
Section: Discussion Of Results Of Studying the Effect Of Berry Extrac...mentioning
confidence: 99%
“…Moisture content was measured using the method of drying (Bozhko et al, 2021). 5 g of the sample was placed in a container and dried to a constant mass at 103°C.…”
Section: Determination Of Moisture Contentmentioning
confidence: 99%